2020
DOI: 10.1093/jee/toaa154
|View full text |Cite
|
Sign up to set email alerts
|

Low Tunnels Reduce Insect Populations, Insecticide Application, and Chewing Insect Damage on Brussels Sprouts

Abstract: Low tunnels covered with spun-bonded fabric (row covers) provide season extension for vegetable production and also afford a physical barrier against airborne insects and other non-soil pests. Brussels sprouts, Brassica oleracea L. group Gemmifera (Brassicaceae), is a popular vegetable in local markets in Virginia; however, unprotected field production is severely affected by insect pest infestation. This study’s objective was to determine the level of protection low tunnels provide against insect infestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Our findings are consistent with prior evidence that row covers reduce insect damage and pest abundance and increase marketable yield in a variety of crops (Moreno et al, 2002;Rojas et al, 2011; Gogo et al, 2014;Kuesel et al, 2019;Nair et al, 2019;Skidmore et al, 2019;Brockman et al, 2020;Acharya et al, 2020b;Athey et al, 2021;Nelson et al, 2023). We found that mesotunnels reduce cucumber beetles significantly during the early developmental stages of cucurbit growth when nets were closed (before flowering).…”
Section: Row Covers Reduce Pests and Increase Yieldsupporting
confidence: 92%
“…Our findings are consistent with prior evidence that row covers reduce insect damage and pest abundance and increase marketable yield in a variety of crops (Moreno et al, 2002;Rojas et al, 2011; Gogo et al, 2014;Kuesel et al, 2019;Nair et al, 2019;Skidmore et al, 2019;Brockman et al, 2020;Acharya et al, 2020b;Athey et al, 2021;Nelson et al, 2023). We found that mesotunnels reduce cucumber beetles significantly during the early developmental stages of cucurbit growth when nets were closed (before flowering).…”
Section: Row Covers Reduce Pests and Increase Yieldsupporting
confidence: 92%
“…The low presence of whiteflies did not increase plant FW or fruit yield. Plants under row cover may have enhanced plant growth and reduced low insect populations (Acharya et al 2020). However, the effect of row cover on the enclosed environment depends on net composition, covering method, and season.…”
Section: Row Covermentioning
confidence: 99%
“…In fall tomatoes, plants on black mulch had higher root zone temperatures, an earlier appearance of tomato spotted wilt virus (TSWV) symptoms, and reduced vegetative growth and fruit yields compared to white mulch (Díaz-Pérez et al 2007). Row and floating covers utilize nets to control insect landings by forming a physical barrier (Acharya et al 2020;Antignus 2011;Ibarra-Jimenez et al 2002;LaTora et al 2022). Nets provide an alternative method for insect management by reducing the need for harmful pesticides (Licciardi et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Aphids are also the important insects of vegetables. The low tunnels reduced insect infestation and chewing herbivory leaf injury to brussels sprouts (Acharya et al, 2020). Aphids could product honey, which effected on the soil (Kyaw et al, 2020).…”
Section: Academicpresmentioning
confidence: 99%